Nonbullous Erythema Multiforme in Hospitalized Children: A 10‐Year Survey. Issue 5 (30th July 2015) - Keller, Noy; Gilad, Oded; Marom, Daphna; Marcus, Nufar; Garty, Ben Zion
Abstract Background Nonbullous erythema multiforme (NBEM) is an acute, immune‐mediated, self‐limiting skin disease with distinctive target lesions. Its pathogenesis is unclear, but most cases are considered to be infection related or drug related. In adults, the main precipitating factor is infection. This study reviewed a 10‐year experience with hospitalized children with NBEM in a tertiary pediatric medical center in Israel with a focus on precipitating factors. Methods The medical files of all children hospitalized from 2001 to 2011 with the diagnosis of NBEM were reviewed. Results Ninety‐seven patients (55 boys and 42 girls) met the inclusion criteria. The mean age was 4.0 years. At least one precipitating factor was recognized in 72 cases; the remainders were classified as idiopathic. The most common factor was drugs (n = 45), particularly penicillin (n = 30), followed by infection with various pathogens (n = 27) including Epstein‐Barr virus (7), group A Streptococcus (n = 6), Mycoplasma pneumoniae (n = 5) and herpes simplex virus (n = 4). Analysis according to age showed that medication was the most common precipitating factor in the first year of life, and infection was as common as drugs in the older age groups (1–18 years). Conclusions Unlike adult NBEM, the majority of pediatric NBEM is associated with medications, especially penicillin. This may be due to the frequent use of antibiotics in children.